ANALISIS TENTANG FAKTOR KESULITAN BELAJAR EKSTREN DI SMPN 10 PUJUD - Efendi, Muhammad Efendi Muhammad; Arlizon, Raja Arlizon Raja; Umari, Tri Umari Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Â  AbstractThis study, entitled "Analysis of Factors learning difficulties Ekstren in SMP 10 Pujud". The purpose of this is: 1) To determine the image factor learning difficulties ekstren in SMP N 10 Pujud. The method used in this research is the type of research is descriptive quantitative approach which aims to provide an overview of the factors that cause learning difficulties ekstren in SMP N 10 Pujud. The findings of this study are: 1) Overview of learning difficulties ekstren factor in SMP 10 Pujud, among other factors picture ekstren learning difficulties in Category High achievement scores are in the 21 to 30 out of a maximum total score of each student as much as 7 people (17.5%), in the category are achievement scores were at 10-20 as many as 32 people (80%), while in the category of low achievement scores were at 0-9 as much as one person (2.5%) .. this means that the picture ekstren learning difficulties in SMP 10 Pujud are in the medium category. 2) Description of factor learning difficulties experienced by students ekstren SMP 10 Pujud, is the most dominant factor ekstren learning difficulties at school. Based on the findings of this study, it can be recommended the following things: 1) To the parents to give more attention to aspects of personality development of students so that future students do not have learning difficulties and have high morale in the study, as well as the physical condition remains in good health so that they can learn the optimal and spirit. 2) To Teachers are encouraged to further remind and enhance the learning activities of students with various learning improvement efforts and cooperation with the parents. 3) For further research, it is advisable to examine more deeply about the attention of parents to assist students' learning activities or efforts to improve the school in cooperation with parents, so that the future can overcome the problems associated with student learning difficulties. Keywords: Learning Difficulties